Perceptions of autistic children's parents about dental care: Preliminary study. Concepción, 2012. - Carolina Hernández; Poliette Oyarzún (Universidad de Concepción., 2014)
The aim of this study was to describe the perceptions of parents of children with autistic disorder (AD) of the school of Association of Parents and Friends of Autistics (ASPAUT) Chiguayante. A cross-sectional and exploratory study was conducted. The target population were the parents of 60 schoolchildren at ASPAUT school. The measuring instrument was a survey of thirty closed questions and one open question. Of the 60 surveys sent out 26 were recovered with varying degrees of response to each of the questions. Almost all children with AD receives dental care, about 1 time per year and mostly by pediatric dentists. There is generally a good perception of the care provided, but the need for specialized in autism spectrum disorders professionals, the existence of specific dental programs and reducing the associated costs are recognized. The issues identified by parents as most relevant for improving care were: a specialized dental care (26.9%), more humane treatment (19.2%) and using distracting techniques (11.5%). 15.4% of parents believe good dental care as well as excellent. In Chile the dental care of this population is just beginning and there are many areas that need improvements.